A Study of the Application of Statistical Sampling to External Auditing (Book). - Bailey, Andrew D.; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "A Study of the Application of Statistical Sampling to External Auditing," by T.W. McRae.